Case series of reports of pruritus and sipuleucel-T submitted to the Food and Drug Administration Adverse Event Reporting System - Graça M. Dores; Silvia Perez-Vilar; Manette T. Niu (BMC, 2019)
Abstract Sipuleucel-T, an autologous active cellular immunotherapy, is indicated for the treatment of asymptomatic or minimally symptomatic castration-resistant prostate cancer. The U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) received a report of pruritus without rash following the second dose of sipuleucel-T in a patient who had otherwise not started any new medications concurrent with the first and second doses of sipuleucel-T. No further sipuleucel-T was administered, but symptoms persisted for at least 6 weeks despite treatment with several medications aimed at symptomatic relief of pruritus. Rash is the only dermatologic adverse event included in the sipuleucel-T U.S. package insert. A search of the FAERS database yielded seven additional U.S. reports of pruritus and sipuleucel-T identified as the primary suspect medication; two of these occurred prior to the administration of sipuleucel-T (following leukapheresis). In data mining analyses, pruritus following sipuleucel-T was not reported more frequently than expected when compared to all other adverse event-drug/biologic combinations in FAERS. Thus, pruritus following sipuleucel-T administration was rarely, but not disproportionately, reported to FAERS. Although we cannot exclude the possibility that diabetes, malignancy, or other conditions may have contributed to pruritus in our index patient, in view of the timing of sipuleucel-T therapy and onset of symptoms, a drug/biologic-related reaction is plausible. In the appropriate clinical scenario, sipuleucel-T (or its components) should not be overlooked as a potential etiological agent in pruritus.